Lost sedilia from the cathedral of St John at 's-Hertogenbosch (Bulletin KNOB, 1993)
In this article a piece of pre-Reformation furniture in the cathedral of 's-Hertogenbosch is discussed. The main source for the original furnishings of the choir and chancel is a series of drawings made by Pieter Jansz. Saenredam during the summer of 1632. One of them shows a wooden construction to the right of the main altar (Fig. 1).Although a number of recent studies have discussed the original decoration of the choir (notes 1 and 2), this detail so far has eluded a satisfactory explanation. It is argued here that it represents now lost sedilia, i.e. a triple seat for the officiating clergy. They have the tripartite structure under a canopy which is characteristic of such pieces of furniture and they are located on the correct liturgical side of the altar.Moreover, by interpreting this detail in the drawing as sedilia, some references in the church accounts can be explained more satisfactorily as well. The construction recorded by Saenredam no doubt dated from the Renaissance period. lts general structure, if not the tripartition, resembles the sedilia in St Cunera's at Rhenen, which originally belonged to the choir-stalls dated 1570 (Figs. 4 and 5).The richly decorated canopy of the structure in St John's parallels that of the pulpit elsewhere in the cathedral, which is generally dated to the period immediately following the iconoclast destructions of 1566 (Fig. 6). According to the church accounts a substantial amount of furniture and carving was commissioned during these years.Several times mention is made of a seat: on March 27, 1567, Joachim Dincx, a carpenter, is paid for boards used on 'the new seat' ('het nyeuwe gestoelte'), and on November 29 of the same year money was spent on beer 'when the seat was erected' ('doen men den stoel richtten'). Until now two candidates for this 'new seat' have been proposed: the bishop's chair and the pulpit.Both claims are unconvincing. The pulpit can be dated on documentary grounds to the years between 1541 and 1566; the canopy, carved by other masters, is probably an addition from the years after 1566. In 1567, then, the pulpit was neither new nor had to be erected. It is generally assumed that the bishop's chair was constructed during the years 1567-1569 as well (Fig. 2).However, it is equally possible that it was made as early as 1563, when Sonnius, the first bishop of 's-Hertogenbosch, made his official entry. Be that as it may, the bishop's chair is an adaption of the existing late Gothic stalls rather than a piece of furniture that had to be specially 'erected'. The interpretation of the documentary evidence becomes less strained if the seat mentioned in the accounts is identified as the sedilia recorded by Saenredam.Considering the similarities with the pulpit's canopy, in 1567 this 'seat' may well have been 'new'. One can easily imagine, too, that the workers wanted a beer after the erection of this monumental structure. In all likelihood the sedilia were executed by Jan Schalcken, a local joiner who according to the accounts carried out a substantial amount of work with his assistants from 1567 to 1570.It may be assumed that he was responsible for the carpentry; for the ornaments and figures a woodcarver would have been contracted a woodcarver. A number of such carvers ('antyxsnijders') are mentioned in the accounts, including Cornelis Bloemaert, the father of the painter Abraham Bloemaert.The high fees he earned suggest that he supplied important work, but unfortunately the carving in the cathedral that has been preserved cannot securely be attributed to anyone in particular. At any rate the quality of the carving on the pulpit's canopy is very high. If that of the sedilia was similar, their loss is all the more regrettable.